The potential function and clinical application of FGF21 in metabolic diseases - Chen, Zhiwei; Yang, Lili; Liu, Yang; Huang, Ping; Song, Haiyan; Zheng, Peiyong (Frontiers in Pharmacology, 2022)
As an endocrine hormone, fibroblast growth factor 21 (FGF21) plays a crucial role in regulating lipid, glucose, and energy metabolism. Endogenous FGF21 is generated by multiple cell types but acts on restricted effector tissues, including the brain, adipose tissue, liver, heart, and skeletal muscle. Intervention with FGF21 in rodents or nonhuman primates has shown significant pharmacological effects on a range of metabolic dysfunctions, including weight loss and improvement of hyperglycemia, hyperlipidemia, insulin resistance, cardiovascular disease, and nonalcoholic fatty liver disease (NAFLD). Due to the poor pharmacokinetic and biophysical characteristics of native FGF21, long-acting FGF21 analogs and FGF21 receptor agonists have been developed for the treatment of metabolic dysfunction. Clinical trials of several FGF21-based drugs have been performed and shown good safety, tolerance, and efficacy. Here we review the actions of FGF21 and summarize the associated clinical trials in obesity, type 2 diabetes mellitus (T2DM), and NAFLD, to help understand and promote the development of efficient treatment for metabolic diseases via targeting FGF21.